FUNGSI FILSAFAT PANCASILA DALAM ILMU PENDIDIKAN DI INDONESIA - Indra Gunawan; Ayu Vinlandari Wahyudi (Balai Diklat Keagamaan Bandung, 2020)
Pancasila has critical, fundamental, rational, systematic, comprehensive thoughts and eventually this system is a value. Pancasila provides fundamental and universal foundations for human beings in social, national, and state. Thus, through the philosophical values of Pancasila, the development of science education is expected to make it as main reference to national education system, which takes place as way to achieve goals and national objectives. The method in this paper is descriptive analytical. The data entered is the most relevant and primary related to the study of Pancasila and education science, then analysis is carried out to produce an ideas. The results demonstrate that educational philosophy of Pancasila as the spirit of national education system should actually lived as source of values and reference to planning the development of science education in Indonesia, both theoretically and practically. Keywords: Educational Philosophy; Science Education; Pancasila; Values.